Developing international alumni relations during the COVID-19 pandemic. Polish case study - Kępski, Piotr (ICAReAlumni Conference Proceedings, 2020)
The aim of the study was to analyse short-term impact of the COVID-19 on international alumni (IA) projects funded by Polish National Agency for Academic Exchange (NAWA). The paper focuses on some immediate effects of the pandemic, and also investigates how Polish stakeholders cope with the problems. The research is mainly based on an online survey conducted among Polish HEIs, but it combines also some desk research. The study indicated that the COVID-19 caused serious problems for IA projects in Poland. Almost ¾ of the respondents estimated the negative effects of the pandemic as very high or high. The most common reaction to the pandemic was virtualisation and digitisation of IA relations. Activities that could be arranged online, especially through the social media and also through webinars, webpages or apps, are deemed as the most effective in the current situation. Despite the difficulties, almost 85% of respondents would once again engage in the IA project. Two key benefits of pursuing IA relations consist in their marketing potential: 1) IA become ambassadors of a HEI brand; 2) they also pursue word of mouth marketing.